Arabic Language in the Current of Modernity: Ideas and Transformations in the National Webinar of the Arabic Language Education Study Program, IAI Hamzanwadi NW East Lombok - Multazam Hajras; Ulyan Nasri (Jurnal Ilmiah Profesi Pendidikan, 2025)
This article explores the dynamics of the Arabic language as it encounters the challenges and demands of modernity, as discussed in the National Webinar held by the Islamic Education Study Program at IAI Hamzanwadi NW East Lombok. The webinar served as an academic platform to examine how Arabic, as both a classical and sacred language, navigates contemporary developments in education, technology, and global communication. The objective of the webinar was to identify critical ideas and transformations in the teaching and learning of Arabic in response to current shifts in educational paradigms. Using qualitative documentation and thematic analysis of the webinar's key sessions and speakers’ insights, this study highlights the relevance of Arabic in modern Islamic education and the innovative methods proposed for its revitalization. Findings reveal a strong academic interest in integrating digital tools, interdisciplinary approaches, and contextual pedagogy to sustain Arabic as a living and dynamic language. The article concludes that embracing modernity does not necessarily undermine the sacred character of Arabic but instead opens opportunities for its broader influence in the modern world.